Relationship between supplier evaluation and family brand strategy Case study in battery factory Al-Waziriya - الشمري سرمد حمزة; العكيلي هالة وسيم (Journal of Economics and Administrative Sciences, 2019)
The research deals with the relationship between supplier evaluation (single variable) and family brand strategy (single variable) a case study in the battery factory-Waziriya, and the fact that the industrial sector represents a cornerstone for building the country’s economy of and their development. The research has been selected on this basis. The problem stems from the lack of business understanding of the real role played by the assessment of the suppliers’ and its strong impact on its reputation and position in the market. The research gains its importance by moving away from traditional marketing style in terms of characteristics related to the resource itself, and the service provided by the factory to customers and keep pace of developments for the purpose of competition and overcoming companies. The research aims at determining the relationship and impact between supplier evaluation and family brand strategy. Based on the research problem two hypotheses are formulated: (There is significant correlation and influence between supplier evaluation and family brand strategy, there is a significant effect of supplier evaluation on family brand strategy).The questionnaire is used to collect data and information related to the research, it is prepared using the fifth Likert scale and is subjected to tests honesty and consistency. It is distributed to a sample of 96 individuals, including a number of department managers, their assistants and a number of managers of divisions and units and their assistants in the factory. In order to analyze the data, SPSS-19 and Excel were used, several statistical tools are used, including the "percentage of the mean, the standard deviation and the coefficient of difference, the Spearman correlation coefficient, and the explanation or explanation coefficient". The statistical methods produce a number of results, most notably the importance of the relationship between supplier evaluation and family brand strategy, as well as the effective impact of supplier evaluation on family brand strategy. Finally, the research presents a number of recommendations, including, preferably the factory to use methods other than advertising in the search for new suppliers for the purpose of evaluation, such as the use of employees or other companies with good working relationship with the company, as well as the need to use an electronic database to document dealings with suppliers to be an easily found reference when needed compared to paper records that consume considerable time and effort.